Moisture determination of cocoa beans by microwave oven - Tiong, Stephen Mee Ing (2023)
A statistical trial was conducted to compare microwave oven and air-heated oven methods for moisture determination of cocoa beans. The findings indicate that both methods are comparable in accuracy but better precision is obtained by the air-heated oven method. The time required for drying of cocoa beans is about 30 minutes by the proposed method as against 16 hours by the conventional technique.